Effect of climate change on “Eichhornia crassipes” infestation in Lake Tana Sub-Basin, North Western Ethiopia - Tesfaye Bayu; Tri Retnaningsih Soeprobowati; Solomon Adissu; Budi Warsito (Sustainable Environment)
Climate change-induced alteration of ecosystem conditions can enable the spread of invasive plant species through both range expansion and the creation of habitats and conditions suitable for newly introduced exotic species. This research tries to evaluate the effect of climate change on ‘Eichhornia crassipes’ intensification in Lake Tana Sub-Basin, North Western Ethiopia. Land use land cover change was analyzed using ArcGIS 10.8 and temperature and rainfall data were interpolated to evaluate the effect of climate change on water hyacinth infestation. The result of the study shows that the area covered by water was decreased, whereas the area covered by water hyacinth was increased by 9.3%. The highest decrease −82.41% in land cover was recorded for savanna forest land which was found in the surrounding area of the lake. A significant amount of water bodies was also converted to wetlands due to the invasion of water hyacinths. The result also shows that areas with high annual temperature readings result in a high rate of water hyacinth invasion. The study also suggests that areas that receive high rainfall were characterized by having a high invasion of water hyacinth. From the study, it is possible to conclude that climate change facilitates the invasion of water hyacinths in Lake Tana. Comprehensive management strategies need to be developed by the government, policymakers, and environmentalists especially considering the positive use of water hyacinth.